Reproductive Freedom, Torture and International Human Rights: Challenging the Masculinization of Torture, By Ronli Sifris - Sveaass, Nora (Torture Journal, 2017)
The title of the book could not be clearer about its key message. In the words of the author, it aims to “contribute to a feminist conceptualization of international human rights by examining restrictions on reproductive freedom through the lens of the right to be free from torture and CIDT [Cruel, Inhumane or Degrading Treatment]” (p8). Sifris’ book draws attention to the grave reality surrounding women’s reproductive freedom in numerous countries and, in particular, the severe restrictions on abortions and the practice of involuntary sterilizations. The author affirms how inhumane and dangerous it is for international law to overlook women’s choices in relation to their own bodies, and the consequences this may have, with many women suffering or dying because of lack of protection. The important question, which is not only raised but discussed in depth, is: how the prohibition against torture can actively be applied in this context?